Penentuan Margin Pembiayaan Murabahah Pada Pembiayaan Murabahah di Baitul Maal Wa Tamwil - Khasanah, Uswatun; Pudail, M; Fitriyani, Yeny (Forum Kerjasama Pendidikan Tinggi, 2024)
This research is motivated by the condition that sharia cooperatives promise a fairer operational system in determining margins. New products such as murabahah contracts are increasingly appearing, including at BMT Nusa Umat Sejahtera, although there are still concerns in the community regarding their optimal implementation. Research problems include the process of determining the murabahah financing margin, the method for calculating the murabahah financing margin, and the main factors that influence the determination of the murabahah financing margin. This research aims to understand the process of determining margin, the method for calculating murabahah margin, and the factors considered in determining margin. The method used was qualitative, the resource persons in this research were 3 manager informants and also admin from BMT Nusa Umat Sejahtera. Research findings show that the murabahah financing margin calculation method uses a flat method, where the margin is fixed throughout the financing period. Factors that influence the determination of murabahah financing margins include the financing process, margin percentage based on collateral, risk and negotiation, while the financing term does not have a significant effect on determining margins at BMT Nusa Umat Sejahtera.